Designing A Conceptual Model For Employee Safety And Work Place Hazards In Relation To Performance - With Reference To Jewellery Manufacturing Firms - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
Organisations are gratified to provide with a safe and healthful environment. The main purpose of health and safety polices is the safe interaction of people and the work environment. Poor working conditions affect employee performance badly. Their health may suffer. Accidents and injuries may multiply causing enormous financial loss to the company. Absence and turnover ratio may grow. Many deaths, injuries and illness occur because of safety violations, poor equipment design or gross negligence. The overall quality of work may suffer. Thus, the research study focuses on protecting employees from workplace hazards particularly among Jewellery manufacturing industries for increasing work performance. A questionnaire of 55 questions is designed to assess employee safety, workplace hazard and performance of employees in Jewellery manufacturing industries. First, workplace hazard assessment include 36 questions; second, employee safety assessment contain 9 questions; and third, performance assessment included 10 questions. In this study among Jewellery industries we have considered six departments namely; wax, filing, buffing, stone setting, steam bath and colouring, which affects employees health and leads to workplace hazards. It is revealed that effective health and safety practices led to high profitability and high productivity. The HR department should have to monitor health and safety of employees daily, coach them to be safety conscious, investigate accidents, observe health and safety behavior of employees, monitor workplace for security problems, communicate with employees to identify potentially difficult employees, and follow safety provisions and security procedures and recommend changes as needed. So, for increasing performance and organisational growth, HR managers should focus on primary health and safety responsibilities towards employee’s health.